2010
DOI: 10.1159/000290452
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Perspectives on a Risk-Benefit Framework for Genetic Testing

Abstract: A key to accelerating the appropriate integration of genomic applications into healthcare in the coming decades will be the ability to assess the tradeoffs between clinical benefits and clinical risks of genetic tests in a timely manner. Several factors limit the ability of stakeholders to achieve this objective, including the lack of direct evidence, the lack of a framework to quantitatively assess risk and benefit, and the lack of a formal analytic approach to assess uncertainty. We propose that a formal, qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…In a previous study, we assessed whether clinical guideline developers and other stakeholders would find benefit-risk modelling a useful adjunct in their deliberations. [35] We found that there is support for a benefit-risk modelling framework as a decision tool, providing for a more structured and transparent consideration. However, there remains some scepticism and debate about the usefulness of the QALY metric.…”
Section: Cer For Devices Diagnostic Tests and Proceduresmentioning
confidence: 88%
“…In a previous study, we assessed whether clinical guideline developers and other stakeholders would find benefit-risk modelling a useful adjunct in their deliberations. [35] We found that there is support for a benefit-risk modelling framework as a decision tool, providing for a more structured and transparent consideration. However, there remains some scepticism and debate about the usefulness of the QALY metric.…”
Section: Cer For Devices Diagnostic Tests and Proceduresmentioning
confidence: 88%
“…4 That study involved a wider range of stakeholders, including consumers, developers, payers, clinicians, and researchers. Our current study included a less-diverse group that had a higher representation of genetic services decision-makers.…”
Section: Discussionmentioning
confidence: 99%
“…12 Drawing from previous research, 4 we identified three key content area codes ( Table 2) to frame the survey questions and stakeholder feedback elicitation and used this scheme to evaluate our notes of the participants' discussion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, he did note that costs are intertwined with health outcomes and thus may be considered as relevant. Stakeholder groups have noted discomfort with using quality-adjusted life years (QALYs) because they do not capture all relevant factors and because of concerns about the methods used to obtain them (Roth et al 2011). Furthermore, Greenberg and Neumann (2011) found that adjusting life years for quality of life does not substantively affect cost per life year ratios, at least for cancerrelated interventions.…”
Section: Develop and Apply Multiple Methods Of Assessing Valuementioning
confidence: 99%